Gandhi in India's literary and cultural imagination
1 online resource (xvi, 266 pages)
Keywords: This book engages with the socio-cultural imaginings of Gandhi in literature, history, visual and popular culture. It explores multiple iterations of his ideas, myths and philosophies, which have inspired the work of filmmakers, playwrights, cartoonists and artists for generations. Gandhi⁰́₉s politics of non-violent resistance and satyagraha inspired various political leaders, activists and movements and has been a subject of rigorous scholarly enquiry and theoretical debates across the globe. Using diverse resources like novels, autobiographies, non-fictional writings, comic books, memes, cartoons and cinema, this book traces the pervasiveness of the idea of Gandhi which has been both idolized and lampooned. It explores his political ideas on themes such as modernity and secularism, environmentalism, abstinence, self-sacrifice and political freedom along with their diverse interpretations, caricatures, criticisms and appropriations to arrive at an understanding of history, culture and society. With contributions from scholars with diverse research interests, this book will be an essential read for students and researchers of political philosophy, cultural studies, literature, Gandhi and peace studies, political science and sociology.